Study the influence of end mill tool geometries toward machining performances - Nurul Amira, Nor Azli (2016)
This thesis deals with study the influence of end mill tool geometries toward machining performances. In this project, two type of end mill tool have been used which are ball nose end mill and bull nose end mill and two type of tool path have been selected which are one way next and zigzag tool path in order to determine the effects of both tool and tool path toward machining performances of surface roughness and machining time. The cutting parameter in this project are spindle speed, feed rate and depth of cut. The machine used in this project is Makino KE55 CNC milling machine. The impact of end mill tool geometry on the surface roughness was determined by the testing the workpiece using Surface Roughness Tester. The machining time was determined by the CATIA V5 software and by the real machining time. Measurement of surface roughness has indicated that the bull nose end mill gives lower surface roughness compare to ball nose end mill when machine an incline surface. In other hand, ball nose end mill give lower surface roughness for free form surface. For machining time, the real machining time is longer than the machining time by the CATIA. The machining data has indicated that ball nose has longer machining time compare to bull nose end mill for machining time of incline and free form surface. In term of tool path, for incline surface zigzag tool path gives better surface than one way tool path and for free form surface one way gives better surface roughness compare to zigzag tool path. This project would help engineer to select the best end mill tool geometry and tool path strategy.